Symptoms and health-related quality of life in patients with newly diagnosed multiple myeloma: a multicenter prospective cohort study. (2nd December 2021) - Suzuki, Nana; Okuyama, Toru; Akechi, Tatsuo; Kusumoto, Shigeru; Ri, Masaki; Inagaki, Atsushi; Kayukawa, Satoshi; Yano, Hiroki; Yoshida, Takashi; Shiraga, Kazuhide; Hashimoto, Hiroya; Aiki, Sayo; et al.
Abstract: Objective: Existing cross-sectional observational studies indicate that patients with multiple myeloma experience negative physical and psychological symptoms and low health-related quality of life. The study aim was to determine symptom prevalence, health-related quality of life and symptoms associated with health-related quality of life in patients with newly diagnosed multiple myeloma. Methods: This multicenter longitudinal cohort study was conducted in four hospitals in Japan. Patients with newly diagnosed multiple myeloma were asked to report their symptom intensity and health-related quality of life using validated questionnaires at three points: at diagnosis (T1), 1 month (T2) and 12 months after diagnosis (T3). Symptoms associated with health-related quality of life were explored using a mixed-effects model. Results: A total of 106 patients completed the assessment at T1. The symptoms more than 30% of patients reported were pain, disturbed sleep and distress at T1, pain, dry mouth, disturbed sleep and fatigue at T2, fatigue, numbness of tingling and pain and numbness or tingling at T3. Pain and depression were significantly associated with health-related quality of life negatively. Conclusions: The finding suggests that more than 30% of multiple myeloma patients suffered from pain and various symptoms and they received suboptimal palliative care within a year after starting initial chemotherapy. Pain and depression should be the main targets of interventions to improve health-related quality of life in this population. Abstract : This longitudinal observational study of patients with newly diagnosed MM showed that patients experienced various symptoms and that pain and depression are symptoms negatively associated with HRQOL.